The insecticidal efficacy comparison of tomato leaves extraction from three solvents for diamondback moth larvae control - ฟักอ่อน นเรต; ตันตาคม ศิริพรรณ (RMUTSB ACADEMIC JOURNAL, 2018)
The objective of this study was to compare the insecticidal efficacy of tomato leaves (Solanum lycopersicum L.) extraction from three solvents; alcohol, acetone and water for controlling the diamondback moth (Plutella xylostella L.). The plant crude extracts were tested with the 2nd-3rd instar larvae of diamondback moth by leaf dipping method at the concentration of 5, 7.5, 10, 15 and 20%. The results showed that the tomato leaves extracted with alcohol gave the best efficacy followed by the extracted with acetone and water respectively. The LC50 at 24 hours of the extracted with alcohol, acetone and water were 13.84, 18.78 and 27.47% (v/v) correspondingly.